2017
DOI: 10.5114/reum.2017.68909
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of ANA antibodies, anticentromere antibodies, and anti-cyclic citrullinated peptide antibodies in patients with primary Sjögren’s syndrome compared to patients with dryness symptoms without primary Sjögren’s syndrome confirmation

Abstract: ObjectivesOur study analyses the prevalence of ANA, anti-SS-A, anti-SS-B, and ACA and ACPA antibodies in patients with pSS and with dryness symptoms without pSS confirmation, and the association of ACPA and ACA antibodies with specific clinical symptoms.Materials and methods113 patients were divided into two groups: I – with diagnosed pSS (N = 75); and II – with dryness without pSS evidence (N = 38). Diagnostics: indirect immunofluorescence (IF; Hep-2 cell line) of antinuclear antibodies (ANA), anti-SS-A anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Recent studies have confirmed our finding that SSa is more relevant than SSb as a diagnostic marker for SS, and that SSb positivity does not affect its classification performance [48,49]. Nevertheless, SSb is associated with particular manifestations and appears to be a sign of increased risk of B-cell expansion, and, like SSa, SSb is associated with younger age and hypocomplementemia [48,49].…”
Section: Discussionsupporting
confidence: 75%
“…Recent studies have confirmed our finding that SSa is more relevant than SSb as a diagnostic marker for SS, and that SSb positivity does not affect its classification performance [48,49]. Nevertheless, SSb is associated with particular manifestations and appears to be a sign of increased risk of B-cell expansion, and, like SSa, SSb is associated with younger age and hypocomplementemia [48,49].…”
Section: Discussionsupporting
confidence: 75%
“…Maslinska et al . 17 reported that the presence of anti-SSB was significantly affected by the higher activity of the disease, which was consistent with the findings of the present study. Additionally, the moderate-high-activity group had positive MRI morphology, X-ray sialography, and lip biopsy findings more frequently compared with the low-activity group, which has not been previously reported.…”
Section: Discussionsupporting
confidence: 94%
“…Anti-CCP is critical in detecting early stage RA patients. Therefore, anti-CCP positive SS patients should be closely monitored for the future development of RA and other overlap syndromes [12,13]. In our study, the frequency of anti-CCP in primary SS was found to be 4.9%.…”
Section: Discussionmentioning
confidence: 54%
“…Conflicting results have been found in studies on the clinical importance of anti-CCP positivity in primary SS. While some of them found that the incidence of arthritis increased in those who were anti CCP positive, other studies do not support this [12,13,[23][24][25].…”
Section: Discussionmentioning
confidence: 96%